PENINGKATAN KINERJA MANAJEMEN TENAGA PENDIDIK - Ghaisani, Larasati; Korokai, Anastasya; Wulandari, Taat; Widiastuti, Anik; Rokhim, Hanif Nur (Jurnal Manajemen Pendidikan, 2025)
Management of improving teacher performance will be appropriate if it is based on good management, starting from planning, implementation, supervision and evaluation, as well as problems found in management. This journal article is written using quantitative methods by taking sources from articles, journals, and books that have been available that discuss and examine the performance of educators/teachers in schools. Efforts that can be made to improve teacher performance include: a) accepting the presence of teachers; b) giving new teaching assignments in accordance with the fields and competencies mastered by the teacher; c) forming and implementing working groups of teachers in the field of study and solving problems that occur in the classroom. Activities designed by school principals in order to improve teacher performance include: 1) teaching and learning activities in the classroom; teachers' scientific meetings; 3) Teacher creativity competitions; 4) Training to support teachers in completing their duties; 5) Motivational seminars 6) Subject teacher meetings.